Actual Problems of Literary Translation: Study of Translation Issues from Uzbek into English - Olimova Dilafruzxon Baxtiyorjon qizi; Ubaydullayeva Maftunaxon Omonboy qizi (Genius Publishing Group, 2022)
The general and specific aspects of the issues of literary translation from Uzbek literature into English, the possibilities of bringing the translated text closer to the original, the achievements and shortcomings in this field, and their causes were studied. A new approach to methodological tools as a unit of literary text was made, and the general changes in them were classified according to the structure of the text, among other factors.
Keywords: Translation; culture; national specifics; mother tongue